A new route to produce starch-based fiber mesh scaffolds by wet spinning and subsequent surface modification as a way to improve cell attachment and proliferation - Tuzlakoglu, K. (2010)
This study proposes a new route for producing fiber mesh scaffolds from a starch-polycaprolactone (SPCL) blend. It was demonstrated that the scaffolds with 77% porosity could be obtained by a simple wet-spinning technique based on solution/precipitation of a polymeric blend. To enhance the cell attachment and proliferation, Ar plasma treatment was applied to the scaffolds. It was observed that the surface morphology and chemical composition were significantly changed because of the etching and functionalization of the fiber surfaces. XPS analyses showed an increase of the oxygen content of the fiber surfaces after plasma treatment (untreated scaffolds O/C:0.32 and plasma-treated scaffolds O/C:0.41). Both untreated and treated scaffolds were examined using a SaOs-2 human osteoblast-like cell line during 2 weeks of culture. The cell seeded on wet-spun SPCL fiber mesh scaffolds showed high viability and alkaline phosphatase enzyme activity, with those values being even higher for the cells seeded on the plasma-treated scaffolds.